2022
DOI: 10.1186/s40959-022-00147-w
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of cardiovascular complications related to immune-checkpoint inhibitor treatment

Abstract: Background The full range of cardiovascular complications related to the use of Immune checkpoint inhibitors (ICI) is not fully understood. We aim to describe the spectrum of cardiovascular adverse events (cvAEs) by presenting our real-world experience of the diagnosis and management of these complications. Methods Two thousand six hundred and forty-seven (2647) patients were started on ICI treatment between 2014 and 2020. Data from 110 patients re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Clinical evidence has indicated that immunotherapy can cause myocarditis, which should be taken seriously. The severity of immune-associated myocarditis varies from mild cases without apparent inflammation to severe cases that may be associated with heart failure, cardiogenic shock, and a high mortality rate in the case of rapidly progressing fulminant myocarditis (98,99). Hu et al concluded that immunotherapy drastically increased the risk of myocardial disease compared with conventional antitumor therapy (100).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence has indicated that immunotherapy can cause myocarditis, which should be taken seriously. The severity of immune-associated myocarditis varies from mild cases without apparent inflammation to severe cases that may be associated with heart failure, cardiogenic shock, and a high mortality rate in the case of rapidly progressing fulminant myocarditis (98,99). Hu et al concluded that immunotherapy drastically increased the risk of myocardial disease compared with conventional antitumor therapy (100).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, documentation of molecular pathways, involved in endothelial dysfunction, can enable the identification of novel druggable targets against endothelial-related functional deficits in cardiovascular diseases [39,76]. Identification and management of Pem-related early coronary endothelial dysregulation are of great clinical value, as in a recent clinical study on ICIinduced CVAEs, vascular-driven CVAEs, such as vasovagal syncope, acute myocardial infarction and microvascular dysfunction, were observed within the spectrum of ICI-induced cardiovascular complications [3]. Therefore, the pharmacological management of ICI-derived early coronary endothelial dysregulation might serve as a druggable target for the mitigation of both cardiac dysfunction and vascular-driven CVAEs by anti-PD-1 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated event rate of immune-related myocarditis was 1.05%, but the median time of development was delayed to 38 days. Another real-world investigation ( 158 ), that included 2647 patients treated with ICIs, revealed cardiovascular irAEs in 89 patients (3.4%), with myocarditis accounting for approximately. 37.1% of cases.…”
Section: Immune-related Adverse Eventsmentioning
confidence: 99%